North American crayfish: A quest for the biggest catch - Caitlin C. Bloomer; Susan B. Adams; Zanethia C. Barnett; Zackary A. Graham; Emmy M. Delekta; David M. Hayes; Zachary J. Loughman; Hugh MacIntosh; M. Worth Pugh; Karen Reed; Nathaniel F. Shoobs; Christopher A. Taylor; et al. (Ecology, 2026)

Synsedimentary mineralization in the Paleoproterozoic McArthur River (HYC) Zn-Pb-Ag deposit, McArthur Basin, Australia - Malcolm W. Wallace; Christopher P. Reed; Ashleigh v.S. Hood; Alexandra V. Turchyn; Nicola Cawood; Maxwell A. Lechte (Precambrian Research, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Tectonically-induced neptunian dykes and breccias of the Paleoproterozoic Teena Dolomite: Significance to stratiform zinc deposits in the McArthur Basin, Australia - Mana Ryuba; Malcolm W. Wallace; Ashleigh v.S. Hood; Christopher P. Reed; Nicola Cawood (Precambrian Research, 2025)

Palaeoecology of the Pliocene large carnivore guild at Hadar, Lower Awash Valley, Ethiopia - Joshua R. Robinson; Ignacio A. Lazagabaster; John Rowan; Margaret E. Lewis; Lars Werdelin; Christopher J. Campisano; Kaye E. Reed (Journal of Human Evolution, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Effects of snake fungal disease (ophidiomycosis) on the skin microbiome across two major experimental scales - Alexander S. Romer; Matthew Grisnik; Jason W. Dallas; William Sutton; Christopher M. Murray; Rebecca H. Hardman; Tom Blanchard; Ryan J. Hanscom; Rulon W. Clark; Cody Godwin; N. Reed Alexander; Kylie C. Moe; et al. (Conservation Biology, 2025)
Emerging infectious diseases are increasingly recognized as a significant threat to global biodiversity conservation. Elucidating the relationship between pathogens and the host microbiome could lead to novel approaches for mitigating disease impacts. Pathogens can alter the host microbiome by inducing dysbiosis, an ecological state characterized by a reduction in bacterial alpha diversity, an increase in pathobionts, or a shift in beta diversity. We used the snake fungal disease (SFD; ophidiomycosis), system to examine how an emerging pathogen may induce dysbiosis across two experimental scales. We used quantitative polymerase chain reaction, bacterial amplicon sequencing, and a deep learning neural network to characterize the skin microbiome of free‐ranging snakes across a broad phylogenetic and spatial extent. Habitat suitability models were used to find variables associated with fungal presence on the landscape. We also conducted a laboratory study of northern watersnakes to examine temporal changes in the skin microbiome following inoculation with Ophidiomyces ophidiicola . Patterns characteristic of dysbiosis were found at both scales, as were nonlinear changes in alpha and alterations in beta diversity, although structural‐level and dispersion changes differed between field and laboratory contexts. The neural network was far more accurate (99.8% positive predictive value [PPV]) in predicting disease state than other analytic techniques (36.4% PPV). The genus Pseudomonas was characteristic of disease‐negative microbiomes, whereas, positive snakes were characterized by the pathobionts Chryseobacterium , Paracoccus , and Sphingobacterium . Geographic regions suitable for O. ophidiicola had high pathogen loads (>0.66 maximum sensitivity + specificity). We found that pathogen‐induced dysbiosis of the microbiome followed predictable trends, that disease state could be classified with neural network analyses, and that habitat suitability models predicted habitat for the SFD pathogen.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

A model for community-driven development of best practices: the Ocean Observatories Initiative Biogeochemical Sensor Data Best Practices and User Guide - Hilary I. Palevsky; Sophie Clayton; Heather Benway; Mairead Maheigan; Dariia Atamanchuk; Roman Battisti; Jennifer Batryn; Annie Bourbonnais; Ellen M. Briggs; Filipa Carvalho; Alison P. Chase; Rachel Eveleth; et al. (Frontiers in Marine Science, 2024)
The field of oceanography is transitioning from data-poor to data-rich, thanks in part to increased deployment of in-situ platforms and sensors, such as those that instrument the US-funded Ocean Observatories Initiative (OOI). However, generating science-ready data products from these sensors, particularly those making biogeochemical measurements, often requires extensive end-user calibration and validation procedures, which can present a significant barrier. Openly available community-developed and -vetted Best Practices contribute to overcoming such barriers, but collaboratively developing user-friendly Best Practices can be challenging. Here we describe the process undertaken by the NSF-funded OOI Biogeochemical Sensor Data Working Group to develop Best Practices for creating science-ready biogeochemical data products from OOI data, culminating in the publication of the GOOS-endorsed OOI Biogeochemical Sensor Data Best Practices and User Guide. For Best Practices related to ocean observatories, engaging observatory staff is crucial, but having a “user-defined” process ensures the final product addresses user needs. Our process prioritized bringing together a diverse team and creating an inclusive environment where all participants could effectively contribute. Incorporating the perspectives of a wide range of experts and prospective end users through an iterative review process that included “Beta Testers’’ enabled us to produce a final product that combines technical information with a user-friendly structure that illustrates data analysis pipelines via flowcharts and worked examples accompanied by pseudo-code. Our process and its impact on improving the accessibility and utility of the end product provides a roadmap for other groups undertaking similar community-driven activities to develop and disseminate new Ocean Best Practices.

Cardiovascular and mood responses to an acute bout of cold water immersion - Emma L. Reed; Christopher L. Chapman; Emma K. Whittman; Talia E. Park; Emily A. Larson; Brendan W. Kaiser; Lindan N. Comrada; Karen Wiedenfeld Needham; John R. Halliwill; Christopher T. Minson (Journal of Thermal Biology, 2023)

Root litter decomposition rates and impacts of drought are regulated by ecosystem legacy - Nichole Reed; Eduardo Dias de Oliveira; Brenda Molano-Flores; Roser Matamala; Christopher J. Whelan; Miquel A. Gonzalez-Meler (Applied Soil Ecology, 2023)

Measurement artifacts in the dithiothreitol (DTT) oxidative potential assay caused by interactions between aqueous metals and phosphate buffer - Jayashree Yalamanchili; Christopher J. Hennigan; Brian E. Reed (Journal of Hazardous Materials, 2023)

A pipeline for testing drug mechanism of action and combination therapies: From microarray data to simulations via Linear-In-Flux-Expressions - Christopher Denaro; Nathaniel J. Merrill; Sean T. McQuade; Logan Reed; Karim Azer; Benedetto Piccoli (Mathematical Biosciences, 2023)

Organic matter sulfurization and organic carbon burial in the Mesoproterozoic - Morgan Reed Raven; Peter W. Crockford; Malcolm S.W. Hodgskiss; Timothy W. Lyons; Christopher J. Tino; Samuel M. Webb (Geochimica et Cosmochimica Acta, 2023)

A science-based policy for managing free-roaming cats - Christopher A. Lepczyk; David C. Duffy; David M. Bird; Michael Calver; Dmitry Cherkassky; Linda Cherkassky; Christopher R. Dickman; David Hunter; David Jessup; Travis Longcore; Scott R. Loss; Kerrie Anne T. Loyd; et al. (Biological Invasions, 2022)

Assessing neophobia and exploration while accounting for social context: an example application in scimitar-horned oryx - Katherine Mertes; Catherine A. Ressijac; Rosana N. Moraes; Lacey F. Hughey; Luisa H. Porto Alegre; Megan Horning; Tara Buk; Arielle Harwood; Lawrence Layman; Christopher Mathews; Morgan Vance; Dolores Reed; et al. (Mammalian Biology, 2022)
Spatial neophobia and exploration are often assessed in nonhuman animals by measuring behavioral responses to novel environments. These traits may especially affect the performance of individuals translocated to novel environments for conservation purposes. Here, we present methods to administer and analyze a minimally invasive novel environment test that accounts for the social context of focal individuals. We used an aerial platform to capture video footage of a captive herd of scimitar-horned oryx ( Oryx dammah ) entering an unfamiliar enclosure. We analyzed footage for seven individually identifiable oryx, scoring their behavioral responses (i.e., latency to enter the enclosure, and movement and posture after entering the enclosure) and social context (i.e., relative position and number of nearby animals). We performed a principal components analysis (PCA) to explore individual traits and responses, and used generalized linear mixed models (GLMMs) to determine the effect of individual traits and social context on individual posture and movement behaviors. Both PCA and GLMMs supported our expectation that social context affects individual behavior: high neighbor density and relative position were negatively related to individual movement, and variation in social context was positively related with head-up postures and movement. Oryx were well differentiated along two principal components that reflected (1) vigilance or caution, and (2) changing social context and age. These methods provide a framework for assessing individual responses to a novel environment in a group setting, which can inform reintroduction and wildlife management efforts, while minimizing interference with animal behavior and management operations.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Changes in tree drought sensitivity provided early warning signals to the California drought and forest mortality event - Rachel M. Keen; Steven L. Voelker; S.‐Y. Simon Wang; Barbara J. Bentz; Michael L. Goulden; Cody R. Dangerfield; Charlotte C. Reed; Sharon M. Hood; Adam Z. Csank; Todd E. Dawson; Andrew G. Merschel; Christopher J. Still (Global Change Biology, 2022)
Climate warming in recent decades has negatively impacted forest health in the western United States. Here, we report on potential early warning signals (EWS) for drought‐related mortality derived from measurements of tree‐ring growth (ring width index; RWI) and carbon isotope discrimination (∆ 13 C), primarily focused on ponderosa pine ( Pinus ponderosa ). Sampling was conducted in the southern Sierra Nevada Mountains, near the epicenter of drought severity and mortality associated with the 2012–2015 California drought and concurrent outbreak of western pine beetle ( Dendroctonus brevicomis ). At this site, we found that widespread mortality was presaged by five decades of increasing sensitivity (i.e., increased explained variation) of both tree growth and ∆ 13 C to Palmer Drought Severity Index (PDSI). We hypothesized that increasing sensitivity of tree growth and ∆ 13 C to hydroclimate constitute EWS that indicate an increased likelihood of widespread forest mortality caused by direct and indirect effects of drought. We then tested these EWS in additional ponderosa pine‐dominated forests that experienced varying mortality rates associated with the same California drought event. In general, drier sites showed increasing sensitivity of RWI to PDSI over the last century, as well as higher mortality following the California drought event compared to wetter sites. Two sites displayed evidence that thinning or fire events that reduced stand basal area effectively reversed the trend of increasing hydroclimate sensitivity. These comparisons indicate that reducing competition for soil water and/or decreasing bark beetle host tree density via forest management—particularly in drier regions—may buffer these forests against drought stress and associated mortality risk. EWS such as these could provide land managers more time to mitigate the extent or severity of forest mortality in advance of droughts. Substantial efforts at deploying additional dendrochronological research in concert with remote sensing and forest modeling will aid in forecasting of forest responses to continued climate warming.

Improving species status assessments under the U.S. Endangered Species Act and implications for multispecies conservation challenges worldwide - Reed F. Noss; Jennifer M. Cartwright; Dwayne Estes; Theo Witsell; Gregg Elliott; Daniel Adams; Matthew Albrecht; Ryan Boyles; Patrick Comer; Chris Doffitt; Don Faber‐Langendoen; JoVonn Hill; et al. (Conservation Biology, 2021)
Despite its successes, the U.S. Endangered Species Act (ESA) has proven challenging to implement due to funding limitations, workload backlog, and other problems. As threats to species survival intensify and as more species come under threat, the need for the ESA and similar conservation laws and policies in other countries to function efficiently has grown. Attempts by the U.S. Fish and Wildlife Service (USFWS) to streamline ESA decisions include multispecies recovery plans and habitat conservation plans. We address species status assessment (SSA), a USFWS process to inform ESA decisions from listing to recovery, within the context of multispecies and ecosystem planning. Although existing SSAs have a single‐species focus, ecosystem‐based research can efficiently inform multiple SSAs within a region and provide a foundation for transition to multispecies SSAs in the future. We considered at‐risk grassland species and ecosystems within the southeastern United States, where a disproportionate number of rare and endemic species are associated with grasslands. To initiate our ecosystem‐based approach, we used a combined literature‐based and structured World Café workshop format to identify science needs for SSAs. Discussions concentrated on 5 categories of threats to grassland species and ecosystems, consistent with recommendations to make shared threats a focus of planning under the ESA: (1) habitat loss, fragmentation, and disruption of functional connectivity; (2) climate change; (3) altered disturbance regimes; (4) invasive species; and (5) localized impacts. For each threat, workshop participants identified science and information needs, including database availability, research priorities, and modeling and mapping needs. Grouping species by habitat and shared threats can make the SSA process and other planning processes for conservation of at‐risk species worldwide more efficient and useful. We found a combination of literature review and structured discussion effective for identifying the scientific information and analysis needed to support the development of multiple SSAs. Article impact statement : Species status assessments can be improved by an ecosystem‐based approach that groups imperiled species by shared habitats and threats.

The Utility of Satellites and Autonomous Remote Sensing Platforms for Monitoring Offshore Aquaculture Farms: A Case Study for Canopy Forming Kelps - Tom W. Bell; Nick J. Nidzieko; David A. Siegel; Robert J. Miller; Kyle C. Cavanaugh; Norman B. Nelson; Daniel C. Reed; Dmitry Fedorov; Christopher Moran; Jordan N. Snyder; Katherine C. Cavanaugh; Christie E. Yorke; et al. (Frontiers in Marine Science, 2020)
The emerging sector of offshore kelp aquaculture represents an opportunity to produce biofuel feedstock to help meet growing energy demand. Giant kelp represents an attractive aquaculture crop due to its rapid growth and production, however precision farming over large scales is required to make this crop economically viable. These demands necessitate high frequency monitoring to ensure outplant success, maximum production, and optimum quality of harvested biomass, while the long distance from shore and large necessary scales of production makes in person monitoring impractical. Remote sensing offers a practical monitoring solution and nascent imaging technologies could be leveraged to provide daily products of the kelp canopy and subsurface structures over unprecedented spatial scales. Here, we evaluate the efficacy of remote sensing from satellites and aerial and underwater autonomous vehicles as potential monitoring platforms for offshore kelp aquaculture farms. Decadal-scale analyses of the Southern California Bight showed that high offshore summertime cloud cover restricts the ability of satellite sensors to provide high frequency direct monitoring of these farms. By contrast, daily monitoring of offshore farms using sensors mounted to aerial and underwater drones seems promising. Small Unoccupied Aircraft Systems (sUAS) carrying lightweight optical sensors can provide estimates of canopy area, density, and tissue nitrogen content on the time and space scales necessary for observing changes in this highly dynamic species. Underwater color imagery can be rapidly classified using deep learning models to identify kelp outplants on a longline farm and high acoustic returns of kelp pneumatocysts from side scan sonar imagery signal an ability to monitor the subsurface development of kelp fronds. Current sensing technologies can be used to develop additional machine learning and spectral algorithms to monitor outplant health and canopy macromolecular content, however future developments in vehicle and infrastructure technologies are necessary to reduce costs and transcend operational limitations for continuous deployment in an offshore setting.

Adaptive capacity in social–ecological systems: a framework for addressing bark beetle disturbances in natural resource management - Stuart Cottrell; Katherine M. Mattor; Jesse L. Morris; Christopher J. Fettig; Pavlina McGrady; Dorothy Maguire; Patrick M. A. James; Jennifer Clear; Zach Wurtzebach; Yu Wei; Andrea Brunelle; Jessica Western; et al. (Sustainability Science, 2020)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Publishing social science research in Conservation Biology to move beyond biology - Tara L. Teel; Christopher B. Anderson; Mark A. Burgman; Joshua Cinner; Douglas Clark; Rodrigo A. Estévez; Julia P.G. Jones; Tim R. McClanahan; Mark S. Reed; Chris Sandbrook; Freya A.V. St. John (Conservation Biology, 2018)

Fossil Giraffidae (Mammalia, Artiodactyla) from Lee Adoyta, Ledi-Geraru, and Late Pliocene Dietary Evolution in Giraffids from the Lower Awash Valley, Ethiopia - John Rowan; Ellis M. Locke; Joshua R. Robinson; Christopher J. Campisano; Jonathan G. Wynn; Kaye E. Reed (Journal of Mammalian Evolution, 2017)

Seascape drivers of M acrocystis pyrifera population genetic structure in the northeast P acific - Mattias L. Johansson; Filipe Alberto; Daniel C. Reed; Peter T. Raimondi; Nelson C. Coelho; Mary A. Young; Patrick T. Drake; Christopher A. Edwards; Kyle Cavanaugh; Jorge Assis; Lydia B. Ladah; Tom W. Bell; et al. (Molecular Ecology, 2015)
At small spatial and temporal scales, genetic differentiation is largely controlled by constraints on gene flow, while genetic diversity across a species' distribution is shaped on longer temporal and spatial scales. We assess the hypothesis that oceanographic transport and other seascape features explain different scales of genetic structure of giant kelp, M acrocystis pyrifera . We followed a hierarchical approach to perform a microsatellite‐based analysis of genetic differentiation in M acrocystis across its distribution in the northeast P acific. We used seascape genetic approaches to identify large‐scale biogeographic population clusters and investigate whether they could be explained by oceanographic transport and other environmental drivers. We then modelled population genetic differentiation within clusters as a function of oceanographic transport and other environmental factors. Five geographic clusters were identified: A laska/ C anada, central C alifornia, continental S anta B arbara, C alifornia C hannel I slands and mainland southern C alifornia/ B aja C alifornia peninsula. The strongest break occurred between central and southern C alifornia, with mainland S anta B arbara sites forming a transition zone between the two. Breaks between clusters corresponded approximately to previously identified biogeographic breaks, but were not solely explained by oceanographic transport. An isolation‐by‐environment ( IBE ) pattern was observed where the northern and southern C hannel I slands clustered together, but not with closer mainland sites, despite the greater distance between them. The strongest environmental association with this IBE pattern was observed with light extinction coefficient, which extends suitable habitat to deeper areas. Within clusters, we found support for previous results showing that oceanographic connectivity plays an important role in the population genetic structure of M acrocystis in the Northern hemisphere.

Recent Trends in Product Development and Regulatory Issues on Impurities in Active Pharmaceutical Ingredient (API) and Drug Products. Part 1: Predicting Degradation Related Impurities and Impurity Considerations for Pharmaceutical Dosage Forms - Karen M. Alsante; Kim Huynh-Ba; Steven W. Baertschi; Robert A. Reed; Margaret S. Landis; Mark H. Kleinman; Christopher Foti; Venkatramana M. Rao; Paul Meers; Andreas Abend; Daniel W. Reynolds; Biren K. Joshi (AAPS PharmSciTech, 2014)

A multi‐decade time series of kelp forest community structure at San Nicolas Island, California (USA) - Michael C. Kenner; James A. Estes; M. Tim Tinker; James L. Bodkin; Robert K. Cowen; Christopher Harrold; Brian B. Hatfield; Mark Novak; Andrew Rassweiler; Daniel C. Reed (Ecology, 2013)
San Nicolas Island is surrounded by broad areas of shallow subtidal habitat, characterized by dynamic kelp forest communities that undergo dramatic and abrupt shifts in community composition. Although these reefs are fished, the physical isolation of the island means that they receive less impact from human activities than most reefs in Southern California, making San Nicolas an ideal place to evaluate alternative theories about the dynamics of these communities. Here we present monitoring data from seven sampling stations surrounding the island, including data on fish, invertebrate, and algal abundance. These data are unusual among subtidal monitoring data sets in that they combine relatively frequent sampling (twice per year) with an exceptionally long time series (since 1980). Other outstanding qualities of the data set are the high taxonomic resolution captured and the monitoring of permanent quadrats and swaths where the history of the community structure at specific locations has been recorded through time. Finally, the data span a period that includes two of the strongest ENSO events on record, a major shift in the Pacific decadal oscillation, and the reintroduction of sea otters to the island in 1987 after at least 150 years of absence. These events provide opportunities to evaluate the effects of bottom‐up forcing, top‐down control, and physical disturbance on shallow rocky reef communities.

The role of intrusions in the formation of Irish-type mineralisation - Jim McCusker; Christopher Reed (Mineralium Deposita, 2013)

Lipidomic Profiling of Phosphocholine Containing Brain Lipids in Mice with Sensorimotor Deficits and Anxiety-Like Features After Exposure to Gulf War Agents - Laila Abdullah; James E. Evans; Alex Bishop; Jon M. Reed; Gogce Crynen; John Phillips; Robert Pelot; Myles A. Mullan; Austin Ferro; Christopher M. Mullan; Michael J. Mullan; Ghania Ait-Ghezala; et al. (NeuroMolecular Medicine, 2012)

Immunomodulatory and Physical Effects of Phospholipid Composition in Vaccine Adjuvant Emulsions - Christopher B. Fox; Susan L. Baldwin; Malcolm S. Duthie; Steven G. Reed; Thomas S. Vedvick (AAPS PharmSciTech, 2012)

The role of MHC class I allele Mamu-A*07 during SIVmac239 infection - Jason S. Reed; John Sidney; Shari M. Piaskowski; Chrystal E. Glidden; Enrique J. León; Benjamin J. Burwitz; Holly L. Kolar; Christopher M. Eernisse; Jessica R. Furlott; Nicholas J. Maness; Andrew D. Walsh; Richard A. Rudersdorf; et al. (Immunogenetics, 2011)

Absolute Calibration in Bass Strait, Australia: TOPEX, Jason-1 and OSTM/Jason-2 - Christopher Watson; Neil White; John Church; Reed Burgette; Paul Tregoning; Richard Coleman (Marine Geodesy, 2011)

The SUMO conjugation pathway in Populus: genomic analysis, tissue-specific and inducible SUMOylation and in vitro de-SUMOylation - Jon M. Reed; Christopher Dervinis; Alison M. Morse; John M. Davis (Planta, 2010)

Molecular characterization of a Hungarian isolate of Tobacco necrosis virus A - Laszlo Krizbai; Maria Nemeth; Vivian Law; Christopher Reed; Aniko Varga; Rozalia Hangyal; Delano James (Archives of Virology, 2010)

Remarkable Amphibian Biomass and Abundance in an Isolated Wetland: Implications for Wetland Conservation - J. WHITFIELD GIBBONS; CHRISTOPHER T. WINNE; DAVID E. SCOTT; JOHN D. WILLSON; XAVIER GLAUDAS; KIMBERLY M. ANDREWS; BRIAN D. TODD; LUKE A. FEDEWA; LUCAS WILKINSON; RIA N. TSALIAGOS; STEVEN J. HARPER; JUDITH L. GREENE; et al. (Conservation Biology, 2006)
Despite the continuing loss of wetland habitats and associated declines in amphibian populations, attempts to translate wetland losses into measurable losses to ecosystems have been lacking. We estimated the potential productivity from the amphibian community that would be compromised by the loss of a single isolated wetland that has been protected from most industrial, agricultural, and urban impacts for the past 54 years. We used a continuous drift fence at Ellenton Bay, a 10‐ha freshwater wetland on the Savannah River Site, near Aiken, South Carolina (U.S.A.), to sample all amphibians for 1 year following a prolonged drought. Despite intensive agricultural use of the land surrounding Ellenton Bay prior to 1951, we documented 24 species and remarkably high numbers and biomass of juvenile amphibians (>360,000 individuals; >1,400 kg) produced during one breeding season. Anurans (17 species) were more abundant than salamanders (7 species), comprising 96.4% of individual captures. Most (95.9%) of the amphibian biomass came from 232095 individuals of a single species of anuran (southern leopard frog [Rana sphenocephala ]). Our results revealed the resilience of an amphibian community to natural stressors and historical habitat alteration and the potential magnitude of biomass and energy transfer from isolated wetlands to surrounding terrestrial habitat. We attributed the postdrought success of amphibians to a combination of adult longevity (often >5 years), a reduction in predator abundance, and an abundance of larval food resources. Likewise, the increase of forest cover around Ellenton Bay from 60% in 2001 probably contributed to the long‐term persistence of amphibians at this site. Our findings provide an optimistic counterpoint to the issue of the global decline of biological diversity by demonstrating that conservation efforts can mitigate historical habitat degradation.

Application of Geospatial Technology to Monitor Forest Legacy Conservation Easements - Kenton Williams; Steven A. Sader; Christopher Pryor; Frank Reed (Journal of Forestry, 2006)
Remote sensing and other geospatial tools are being applied to monitor large working forest conservation easements and to assist office and field users to improve the efficiency of required monitoring. Two USDA-Forest Legacy Program conservation easements in northern New England are included as case studies to describe how to acquire geospatial data and apply these tools to monitor selected easement features. Much of the remote sensing and geographical information system (GIS) data are free or low cost and functional software capable of viewing, querying, and making measurements on images and maps can be acquired from public sources. A high-resolution, digital image management system linked to satellite imagery and the GIS database is presented. Finally, the geospatial monitoring tools on a handheld personal data assistant device for field users are demonstrated.

Modeling Continental Shelf Formation in the Adriatic Sea and Elsewhere - Lincoln Pratson; John Swenson; Albert Kettner; Juan Fedele; George Postma; Alan Niedoroda; Carl Friedrichs; James Syvitski; Chris Paola; Mike Steckler; Eric Hutton; Christopher Reed; et al. (Oceanography, 2004)

Sediment Dynamics in the Adriatic Sea Investigated with Coupled Models - Christopher Sherwood; Jeffrey Book; Sandro Carniel; Luigi Cavaleri; Jacopo Chiggiato; Himangshu Das; James Doyle; Courtney Harris; Alan Niedoroda; Henry Perkins; Pierre-Marie Poulain; Julie Pullen; et al. (Oceanography, 2004)

Zn-Pb mineralisation in the Silvermines district, Ireland: a product of burial diagenesis - Christopher P. Reed; Malcolm W. Wallace (Mineralium Deposita, 2004)

A strategy for the integration of QTL, gene expression, and sequence analyses - Robert Hitzemann; Barry Malmanger; Cheryl Reed; Maureen Lawler; Barbara Hitzemann; Shannon Coulombe; Kari Buck; Brooks Rademacher; Nicole Walter; Yekatrina Polyakov; James Sikela; Brenda Gensler; et al. (Mammalian Genome, 2003)

Diagenetic evidence for an epigenetic origin of the Courtbrown Zn–Pb deposit, Ireland - Christopher P. Reed; Malcolm W. Wallace (Mineralium Deposita, 2001)